Outcomes of Microbial Keratitis Cases Resistant to Antimicrobials in Sydney, Australia. Issue 5 (5th May 2022) - Cabrera-Aguas, Maria; Khoo, Pauline; Watson, Stephanie L.
Abstract : Purpose: The purpose of this study was to describe demographics, predisposing factors, clinical features, treatment, and outcomes of microbial keratitis cases resistant to antimicrobials. Methods: A retrospective case series was conducted. All patients with microbial keratitis resistant to antimicrobials who underwent a corneal scrape and culture from 2012 to December 2016 at the Sydney Eye Hospital were included. Cases were identified from pathology and hospital coding data. Coagulase-negative staphylococci (CoNS), Staphylococcus aureus (S. aureus), and Corynebacterium spp. resistant to cefalotin, chloramphenicol, ciprofloxacin, or gentamicin were analyzed. Results: One hundred fifteen episodes had a resistant CoNS, 24 S. aureus, and 12 C orynebacterium spp. Antimicrobial resistance was associated with older women (67%, median age 83 years) with Corynebacterium spp. ( P < 0.001), corneal graft, and previous topical steroid use. Larger epithelial defects ( P = 0.203) and infiltrates ( P = 0.180) were more likely to be associated with Corynebacterium spp., but not statistically significant. At the initial and final visits, resistant S. aureus (75% vs. 67%) and Corynebacterium spp. (78% vs. 80%) cases were more likely to be classified as blind (>3/60) compared with CoNS (45% vs. 28%) ( P = 0.011 vs. P = 0.004). Corneal perforation occurred more often in resistant S. aureus cases ( P < 0.001), whereas slow and nonhealing epithelial defects needing other procedures were more likely to occur with resistant Corynebacterium spp. ( P < 0.001). Conclusions: Patients with resistant CoNS were younger and presented with smaller ulcers and moderate vision loss. Visual and clinical outcomes were significantly better for resistant CoNS than for those with resistant S. aureus or Corynebacterium spp.